Effect of Microphone Configuration and Sound Source Location on Speech Recognition for Adult Cochlear Implant Users with Current-Generation Sound Processors. - Dwyer, Robert T.; Roberts, Jillian; Gifford, René H. (Journal of the American Academy of Audiology, 2020)
Background Microphone location has been shown to influence speech recognition with a microphone placed at the entrance to the ear canal yielding higher levels of speech recognition than top-of-the-pinna placement. Although this work is currently influencing cochlear implant programming practices, prior studies were completed with previous-generationmicrophone and sound processor technology. Consequently, the applicability of prior studies to current clinical practice is unclear. Purpose To investigate how microphone location (e.g., at the entrance to the ear canal, at the top of the pinna), speech-source location, and configuration (e.g., omnidirectional, directional) influence speech recognition for adult CI recipients with the latest in sound processor technology. Research Design Single-center prospective study using a within-subjects, repeated-measures design. Study Sample Eleven experienced adult Advanced Bionics cochlear implant recipients (five bilateral, six bimodal) using a Naída CI Q90 sound processor were recruited for this study. Data Collection and Analysis Sentences were presented from a single loudspeaker at 65 dBA for source azimuths of 0°, 90°, or 270° with semidiffuse noise originating from the remaining loudspeakers in the R-SPACE array. Individualized signal-to-noise ratios were determined to obtain 50% correct in the unilateral cochlear implant condition with the signal at 0°. Performance was compared across the following microphone sources: T-Mic 2, integrated processor microphone (formerly behind-the-ear mic), processor micro- phoneþ T-Mic 2, and two types of beamforming: monaural, adaptive beamforming (UltraZoom) and binaural beamforming (StereoZoom). Repeated-measures analyses were completed for both speech recognition and microphone output for each microphone location and configuration as well as sound source location. A two-way analysis of variance using mic and azimuth as the independent variables and output for pink noise as the dependent variable was used to characterize the acoustic output characteristics of each microphone source. Results No significant differences in speech recognition across omnidirectional mic location at any source azimuth or listening condition were observed. Secondary findings were (1) omnidirectional microphone configurations afforded significantly higher speech recognition for conditions in which speech was directed to 90° (when compared with directional microphone configurations), (2) omnidirectional micro- phone output was significantly greater when the signal was presented off-axis, and (3) processor microphone output was significantly greater than T-Mic 2 when the sound originated from 0°, which contributed to better aided detection at 2 and 6 kHz with the processor microphone in this group. Conclusions Unlike previous-generation microphones, we found no statistically significant effect of microphone location on speech recognition in noise from any source azimuth. Directional microphones significantly improved speech recognition in the most difficult listening environments.